Comparative study of serum cholesterol level in obese and non-obese adults in peripheral institution of Jammu region - Kaur, Taranjot; Kotwal, Shivwani; Kalsi, Poonam; Gadda, Irfan R. (International Journal of Research in Medical Sciences, 2025)
Background: The increasing prevalence of obesity in India has a direct correlation with the increasing prevalence of obesity related co-morbidities; hypertension, dyslipidaemia, type 2 diabetes mellitus (T2DM), stroke & cardiovascular disease (CVD). The objective of this study was to compare the Serum lipid profile of obese and non-obese patients and to focus on the frequency of dyslipidaemia in these two groups. Methods: This was a prospective comparative study. in which 100 people were taken and further divided into 2 groups, (Group 1was 50 obese and group 2 was 50 non-obese). Results: On analysis of the physical characteristics of the 50 obese subjects, the mean age (years) was 43.64; the mean weight (kg) was 90.12, the mean height (cm) was159.44; the mean BMI (kg/m2) was 35.42 while on analysis of the physical characteristics of the 50 non-obese subjects, the mean age (years) was 42.62; the mean weight (kg) was 58.2; the mean height (cm) was 158; the mean BMI (kg/m2) was 23.14. The total cholesterol was significantly higher (222 mg/dl) in obese group in comparison with the non-obese group (210 mg/dl), with p value of 0.239. Triglycerides were also significantly higher (205 mg/dl) in obese group compared to the non-obese group (146 mg/dl) with p value of <0.001. LDL was also found to be significantly higher (137.5440 mg/dl) in group 1 compared to the group 2 (113.5440 mg/dl), with a p value of p<0.001. But a significantly lower value (38.1560) was obtained in obese group compared to the non-obese group (55.0200), p<0.001 for HDL-C. Conclusions: Obesity is associated with an increase in the incidence of coronary heart disease, congestive heart failure and strokes and also leads to increase in the values of harmful lipid like total cholesterol, TG and LDL levels. Early and immediate interventional measures like increase in physical activity, healthy dietary habits and regular surveillance are required in order to prevent development of irreversible dangerous complications.